Reaction Ball Feasibility Survey as Advisory Learning Physical Education By Primary School Teachers Of Sleman District - fajar setyo pranyoto (JSH: Journal of Sport and Health, 2020)
This research was motivated by the lack of physical education learning facilities to improve eye, hand and foot coordination. This study aims to see the feasibility of reaction balls as a means of learning eye, hand and foot coordination in physical education. This research is a quantitative research. The subjects of this study were elementary school teachers who taught in Sleman Regency and were obtained by random sampling. Data instrumentation using questionnaires and evaluation sheets. The data analysis technique used quantitative descriptive analysis. Research data in the form of product quality, suggestions, and qualitative improvements, and quantitative data were processed using descriptive statistics. The results showed that the reaction field test tested on elementary teachers who taught in Sleman Regency showed "very good" criteria with a mean score of 4.21. It can be perfected that the development of the reaction ball is suitable for use as a learning tool to improve reactions, eye, hand and foot coordination